126k views
3 votes
(cos x - (sqrt 2)/2)(sec x -1)=0

I. Use the zero product property to set up two equations that will lead to solutions to the original equation.

II. Use a reciprocal identity to express the equation involving secant in terms of sine, cosine, or tangent. 

III. Solve each of the two equations in Part I for x, giving all solutions to the equation.

User Vershov
by
5.6k points

2 Answers

7 votes


(\cos x-(√(2))/(2))(\sec x-1)=0 [/tex]


=(\cos x-(1)/(√(2)))(\sec x-1)=0 [/tex]


((√(2)\cos x-1))/(√(2))((1)/(\cos x\ )-1)=0

(Reciprocal Identity)


((^(√(2)\\cos x-1))/(^(√(2))))((1-\cos x)/(\cos x))=0


(^((√(2)\cos x-1)))/(√(2))((1-\cos x))/(\cos x)=0


(√(2)\cos x-1}){(1-\cos x)}=0 (ZeroProduct Property)


√(2)\cos x-1=0


√(2)\cos x=1


\cos x=(1)/(√(2))


x=(\Pi )/(4)

and


1-\cos x=0


\cos x=1


x=0

x=0 and x=
(\Pi )/(4) are the solutions.

User Joej
by
5.9k points
5 votes

Answer and explanation :

Given :
(\cos x-(√(2))/(2))(\sec x-1)=0

To find :

I. Use the zero product property to set up two equations that will lead to solutions to the original equation.

Solution :

The zero product property state that,

If
x* y=0 then x=0 or y=0 (or both x=0 and y=0)

Applying zero product property we get,


(\cos x-(√(2))/(2))(\sec x-1)=0


(\cos x-(√(2))/(2))=0\text{ or }(\sec x-1)=0

The two equations form is


\cos x-(√(2))/(2)=0....(1)


\sec x-1=0 ......(2)

II. Use a reciprocal identity to express the equation involving secant in terms of sine, cosine, or tangent.

Solution :

The reciprocal identity is flipping of a number,

The reciprocal of secant is 1 by cosine


sec x=(1)/(cos x)

Substitute in the given equation,


(\cos x-(√(2))/(2))((1)/(cos x)-1)=0

III. Solve each of the two equations in Part I for x, giving all solutions to the equation

Solution :

The two equations form is


\cos x-(√(2))/(2)=0....(1)


\sec x-1=0 ......(2)

Solving equation (1)


\cos x-(√(2))/(2)=0


\cos x-{1}\frac{√(2)}=0


\cos x={1}\frac{√(2)}


\cos x=\cos (\pi)/(4)


x=(\pi)/(4)

Solving equation (2)


\sec x-1=0


\sec x=1


\sec x=\sec 0


x=0

Therefore, The solutions of the equation is
x=0,(\pi)/(4)

User Zona
by
5.0k points